From object to experience : the new culture of architectural design - Mallgrave, Harry Francis (Bloomsbury Academic, An imprint of Bloomsbury Publishing Plc, 2018)
"Harry Francis Mallgrave combines a history of ideas about architectural experience with the latest insights from the fields of neuroscience, cognitive science and evolutionary biology to make a powerful argument about the nature and future of architectural design. Today, the sciences have granted us the tools to help us understand better than ever before the precise ways in which the built environment can affect the building user's individual experience. Through an understanding of these tools, architects should be able to become better designers, prioritizing the experience of space - the emotional and aesthetic responses, and the sense of homeostatic well-being, of those who will occupy any designed environment. In From Object to Experience, Mallgrave goes further, arguing that it should also be possible to build an effective new cultural ethos for architectural practice. Drawing upon a range of humanistic and biological sources, and emphasizing the far-reaching implications of new neuroscientific discoveries and models, this book brings up-to-date insights and theoretical clarity to a position that was once considered revolutionary but is fast becoming accepted in architecture."--Bloomsbury Publishing